2020
DOI: 10.1515/sjpain-2020-0082
|View full text |Cite
|
Sign up to set email alerts
|

Above and beyond emotional suffering: the unique contribution of compassionate and uncompassionate self-responding in chronic pain

Abstract: ObjectivesStudies have shown that self-compassion plays a protective role against depression in women with chronic pain (CP). However, the majority of studies in CP have used the total score of the self-compassion scale (SCS), which have raised concerns due to potential overlap, not only between the uncompassionate self-responding factors and psychopathology, but also between self-compassion as a whole and other well-known psychological processes (e.g., mindfulness, acceptance, psychological flexibility). This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
1
2
0
1
Order By: Relevance
“…In two separate samples of non-clinical youth, it was found that the total self-compassion score (as measured with either the full-length or the short form of the SCS) was significantly and substantially negatively correlated with symptom measures of anxiety and depression (all r ’s between -0.52 and -0.64), thus suggesting a clear-cut ‘protective effect.’ Yet, when analyzing the separate contributions of the positive and negative self-compassion components, the data convincingly showed that this observed ‘protective effect’ was driven by the reversed negative self-compassion components (i.e., vulnerability) and that the true shielding effect of the positive self-compassion components appeared to be very modest (when discarding the effect of the negative self-compassion components) or almost nonexistent (when controlling for other vulnerability and protective variables such as neuroticism, extraversion, and self-esteem). Similar findings have been documented in research studying the differential effects of positive and negative self-compassion components in adult populations suffering from depression (Körner et al, 2015 ), eating disorders (Bicaker & Racine, 2022 ), and chronic pain (Carvalho et al, 2020 ). Such findings again cast doubt on the protective shield that these positive self-compassion ought to have.…”
Section: Discussionsupporting
confidence: 80%
“…In two separate samples of non-clinical youth, it was found that the total self-compassion score (as measured with either the full-length or the short form of the SCS) was significantly and substantially negatively correlated with symptom measures of anxiety and depression (all r ’s between -0.52 and -0.64), thus suggesting a clear-cut ‘protective effect.’ Yet, when analyzing the separate contributions of the positive and negative self-compassion components, the data convincingly showed that this observed ‘protective effect’ was driven by the reversed negative self-compassion components (i.e., vulnerability) and that the true shielding effect of the positive self-compassion components appeared to be very modest (when discarding the effect of the negative self-compassion components) or almost nonexistent (when controlling for other vulnerability and protective variables such as neuroticism, extraversion, and self-esteem). Similar findings have been documented in research studying the differential effects of positive and negative self-compassion components in adult populations suffering from depression (Körner et al, 2015 ), eating disorders (Bicaker & Racine, 2022 ), and chronic pain (Carvalho et al, 2020 ). Such findings again cast doubt on the protective shield that these positive self-compassion ought to have.…”
Section: Discussionsupporting
confidence: 80%
“…The current study is part of a larger one that focused on the relationship between self-compassion, pain, psychopathology, and psychological flexibility processes in CP. Specifically, the sample in the present clinical study (n=16) partly overlaps with the sample (n=49) of a published cross-sectional study [24] (which is composed of the baseline scores of the 16 participants who are part of the current study, as well as participants who were not able or interested to participate in the current clinical study, but who agreed to participate in the crosssectional study).…”
Section: Participantsmentioning
confidence: 99%
“…Все вище сказане складає таке проблемне «поле» для досліджень як «пам'ять про біль»: ця інформація закодована у вигляді структурних або функціональних змін у ноцицептивній системі та інших нейрональних структурах, що може призвести до змін у соматосенсорній обробці ноцицептивної інформації та нейроповедінкових змін у майбутньому. Складність діагностики при синдроми хронічного болю у дітей обумовлена ще й тим, що психогенний компонент хронічного больового синдрому може поєднуватися з соматичним (ноцицептивним або нейропатичним) [4].…”
unclassified